Coexistence of Infective Endocarditis and Recurrent Acute Rheumatic Fever: A Case Report - Kino, Kino; Hariyanto, Didik; Fernando, Harben; Fahlevi, Indra (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2025)
Background: Infective endocarditis (IE) and recurrent acute rheumatic fever (ARF) are two serious cardiovascular conditions frequently associated with rheumatic heart disease (RHD). Their coexistence complicates diagnosis and management due to overlapping clinical features such as fever, migratory arthritis, and valvular dysfunction. This case report aims to elucidate the clinical presentation, diagnostic challenges, and treatment strategies in a pediatric patient with coexisting IE and recurrent ARF. Methods: A detailed clinical case study was conducted involving a 10-year-old boy with a history of RHD presenting with joint pain and intermittent fever. Diagnostic evaluations included physical examination, laboratory investigations (including blood cultures and antistreptolysin O titers), and serial transthoracic echocardiography. Therapeutic interventions combined targeted intravenous antibiotics, corticosteroids, and secondary prophylaxis with benzathine penicillin G. Multidisciplinary consultations were employed to optimize management. Results: The patient exhibited echocardiographic evidence of mitral valve vegetations along with severe mitral regurgitation. Blood cultures remained negative, likely due to prior antibiotic exposure. Elevated antistreptolysin O titers confirmed recent streptococcal infection supporting recurrent ARF diagnosis. Clinical improvement was observed with symptom resolution and reduction in vegetation size on follow-up echocardiography. Multimodal therapy was well-tolerated, preventing further complications. Conclusion: This case highlights the diagnostic complexity and therapeutic balancing act required in managing coexisting IE and recurrent ARF in children with RHD. Early recognition through comprehensive evaluation and integrated treatment combining antimicrobial and immunomodulatory approaches can improve outcomes. Continued vigilance and multidisciplinary care are essential for preventing morbidity in this high-risk population.